Moderate to vigorous physical activity interactions with genetic variants and body mass index in a large US ethnically diverse cohort. Issue 2 (25th March 2013) - Richardson, A. S.; North, K. E.; Graff, M.; Young, K. M.; Mohlke, K. L.; Lange, L. A.; Lange, E. M.; Harris, K. M.; Gordon‐Larsen, P.
Summary What is already known about this subject Genome‐Wide Association Studies have successfully identified numerous genetic loci that influence body mass index in European‐descent middle‐aged adults. Adolescence is a high‐risk period for the development of adult obesity and severe obesity. Physical activity is one of the most promising behavioural candidates for preventing and reducing weight gain, particularly among youth. What this study adds An examination of the joint association between 41 of the well‐established obesity susceptibility single‐nucleotide polymorphisms with <5 vs. ≥5 bouts of moderate to vigorous physical activity (MVPA) per week in relation to body mass index (BMI)‐for‐age Z‐score in a nationally representative sample of European American, African–American and Hispanic American adolescents. Three nominally significant interactions (P < 0.05) varied by race/ethnicity. Overall, the estimated effect of the risk allele on BMI‐for‐age Z‐score was greater in individuals with <5 than those with ≥5 bouts MVPA per week. Background Little is known about the interaction between genetic and behavioural factors during lifecycle risk periods for obesity and how associations vary across race/ethnicity. Objective The objective of this study was to examine joint associations of adiposity‐related single‐nucleotide polymorphisms (SNPs) and moderate to vigorous physical activity (MVPA) with body mass index (BMI) in a diverse adolescent cohort. Methods Using data from the National Longitudinal Study of Adolescent Health (n = 8113: Wave II 1996; ages 12–21, Wave III; ages 18–27), we assessed interactions of 41 well‐established SNPs and MVPA with BMI‐for‐age Z‐scores in European Americans (EA; n = 5077), African–Americans (AA; n = 1736) and Hispanic Americans (HA; n = 1300). Results Of 97 assessed, we found nominally significant SNP–MVPA interactions on BMI‐for‐age Z‐score in EA at GNPDA2 and FTO and in HA at LZTR2/SEC16B. In EA, the estimated effect of the FTO risk allele on BMI‐for‐age Z‐score was lower (β = −0.13; 95% confidence interval [CI]: 0.08, 0.18) in individuals with ≥5 vs. <5 (β = 0.24; CI: 0.16, 0.32) bouts of MVPA per week (P for interaction 0.02). Race/ethnicity‐pooled meta‐analysis showed nominally significant interactions for SNPs at TFAP2B, POC5 and LYPLAL1. Conclusions High MVPA may attenuate underlying genetic risk for obesity during adolescence, a high‐risk period for adult obesity.